1982
DOI: 10.3102/00346543052001123
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self and Achievement/Performance Measures

Abstract: This meta-analysis examines the relationship between the various self-measures and measures of performance and achievement. The statistical results of 128 studies are transformed to a common measure, namely, correlation coefficients. These studies represent a total sample of 202,823 persons and produce a data base of 1,136 correlations between self-ratings and performance measures. A range in the relationship of —.77 to .96 was reported with an “average” correlation of .21. It was found that this average relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
204
3
8

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(253 citation statements)
references
References 19 publications
26
204
3
8
Order By: Relevance
“…There are two different views for the studies examining the relationship of self-esteem and academic performance. One side of the research emphasized that academic performance is an important predictor of self-esteem (AlvesMartins et al, 2002;Bowles, 1999;Filozof et al, 1998;Hoge et al, 1995), while the others indicated that self-esteem is a determinant of academic performance (Chapman, 1988;Hansford & Hattie, 1982;Marsh et al, 1988). Both views were tested in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two different views for the studies examining the relationship of self-esteem and academic performance. One side of the research emphasized that academic performance is an important predictor of self-esteem (AlvesMartins et al, 2002;Bowles, 1999;Filozof et al, 1998;Hoge et al, 1995), while the others indicated that self-esteem is a determinant of academic performance (Chapman, 1988;Hansford & Hattie, 1982;Marsh et al, 1988). Both views were tested in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has often been suggested that academic achievement is closely related to self-esteem (Osborne, 1997;Pullmann & Allik, 2008;Suk Wai Wong & Watkins, 2001;Stupniskyet, Renaud, Perry, Ruthig, Haynes, & Clifton, 2007;Whitesell, Mitchell, & Spicer, 2009), nevertheless, considering the literature, this relationship is more complicated than it is thought to be. Some researchers asserted that self-esteem affects academic achievement (Chapman, 1988;Hansford & Hattie, 1982;Marsh, Byrne, & Shavelson, 1988), however some others claim it is affected by academic achievement (Alves-Martinset, Peixoto, Gouveia-Pereira, Amaral, & Pedro, 2002;Baumeister, Campbell, Krueger, & Vohs, 2003;Bowles, 1999;Filozof, Albertin, Jones, Steme, Myers, & McDermott, 1998;Hoge, Smit, & Crist, 1995). It can be concluded that while self-esteem affects academic achievement, it is affected by academic achievement as well.…”
Section: Self-esteem and Academic Achievementmentioning
confidence: 99%
“…Academic self-esteem is also closely tied to academic achievement (e.g. Falchikov and Boud 1989;Hansford and Hattie 1982;Mabe and West 1982;Zell and Krizan 2014). This positive correlation does not necessarily imply causality (Marsh 1990b).…”
Section: Implications For a Causal Relationship Between Academic Selfmentioning
confidence: 99%
“…Öğrencilerin özgüveni ise öğrencilerin motivasyonlarını etkilemektedir. Öğrenmeye yönelik motivasyon başarabilme duygusunu da kapsadığı için öğrencilerin kendine güvenlerinin, motivasyonlarıyla yakından ilişkili olduğu, derslere aktif bir şekilde katılmalarını ve dolayısıyla başarılarını etkilediği belirtilmektedir (Hansford ve Hattie, 1982;Singh vd., 2002). Bu bağlamda, bu değişken alanyazındaki çeşitli çalışmaların ilgi odağı olmuş, gerek ulusal çalışmalarda (Akyüz, 2014;Demir ve Kılıç, 2010) gerekse uluslararası çalışmalarda (Arıkan vd., 2016;Chen, 2013) matematikte kendine güvenin başarıyı olumlu yönde etkilediği bulunmuştur.…”
Section: öğRenci Düzeyi Duyuşşal öZelliklerunclassified